Odpowiedź:
a)
[(-1 1/3)⁻³]² * (4/3)⁴ = [(-2/3)⁻³]² * 256/81 = [(1/(-2/3))³]² * 256/81 = [1/(-8/27)]² * 256/81 = 1/(64/729) * 256/81 = (256/81) / (64/729) = (256/81) * (729/64) = (256/1) * (9/64) = (4/1) * (9/1) = 4*9 = 36
b)
[tex]\frac{\sqrt{5} * 125^\frac{2}{3} * (\frac{1}{5})^{-2}}{25^\frac{-1}{2}} = \frac{5^\frac{1}{2} * 5^\frac{6}{3} * 5^{2}}{5^\frac{-2}{2}} = \frac{5^\frac{1}{2} * 5^2 * 5^{2}}{5^{-1}} = \frac{5^{\frac{1}{2}+2+2}}{5^{-1}} = \frac{5^{(4 \frac{1}{2})}}{5^{-1}} = 5^{(4 \frac{1}{2}) - (-1)} = 5^{(4 \frac{1}{2}) + 1} = 5^{(5 \frac{1}{2})} = 5^{(\frac{11}{2})} = \sqrt{5^{11}} = 6987,712...[/tex]